Efektifitas Mobile Applications terhadap Self-Management pada Pasien dengan Kaki Diabetik - Ikawati, Dewi; Pahria, Tuti; Kurniawan, Titis (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This study aims to map the influence of mobile applications as self-management support in management of diabetic feet. This research uses a scoping review method by entering keywords into the CINAHL, Pubmed, and Scopus databases. The research results show that mobile applications are effectived in increasing knowledge, self-care behavior, self-efficacy, compliance with self-care foot care, eating behavior, reducing wound/ulcer recurrence rates, and cost-effectiveness. The effectiveness of mobile applications can be used as a strategy in providing interventions to support self-management in the management of diabetic feet. The use of mobile applications has an impact on improving independent foot care management as well as increasing knowledge of diabetic foot care so that it has benefits in controlling glycemia, increasing adherence to diet, and increasing physical exercise. In conclusion, Mobile application-based based programs had the potential to improve self-management in diabetic foot patients. Keywords: Diabetic Foot, Mobile Applications, Self-Management